INTERCULTURAL COMMUNICATION AND SOCIAL IDENTITY FORMATION OF UNDOCUMENTED INDONESIAN MIGRANT CHILDREN IN MALAYSIA (Pena Cendekia Insani, 2026)
This study examines intercultural communication practices among undocumented Indonesian migrant children in Malaysia and explains how these practices contribute to social identity formation under conditions of legal vulnerability. Using a qualitative case study design, the research was conducted at a non-formal learning center in Klang, Selangor, involving ten children aged 12–17 years, two educators, and one coordinator. Data were collected through participant observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that children’s intercultural communication is reflected in multilingual practices, code-switching, and communication accommodation strategies. Convergence emerges as the dominant adaptive strategy, not merely as a voluntary attempt to build social closeness, but also as a response to structural constraints produced by undocumented status. This legal vulnerability limits children’s confidence to express Indonesian identity in public spaces and encourages situational identity negotiation. Meanwhile, the learning center functions as a safe space that enables children to maintain cultural belonging, use Indonesian more openly, and negotiate their identity beyond public restrictions. The study contributes to intercultural communication studies by positioning undocumented status as a structural factor that shapes communication adaptation and social identity formation among migrant children.